Analysis of compensation and work motivation on employee performance at PT solomon indo global - Zebua, Siles; Oktafiani, Fida (International Journal of Applied Finance and Business Studies, 2024)
The main reason for this research is to analyze the impact of compensation and work motivation on employee performance. Recognizing that motivated employees are crucial for achieving organizational goals, this study focuses on how various compensation elements as well as motivation affect performance. The methodology involves a quantitative approach, collecting data through questionnaires distributed to 52 employees, supplemented by interviews with two respondents. Data are analyzed statistically to examine the correlation between compensation, motivation, and performance using SPSS and Excel. This research shown that motivation and compensation have a significant effect simultaneously. But partially, compensation and motivation have a positive impact on performance, motivation tend to have more significant effect on performance compare to compensation.